Students’ participation in the development of the pedagogical project. - Freitas e Silva Maia, Natália Maria; Teixeira Nunes, Benevina Maria Vilar; Batista Moura, Maria Eliete (Investigación y Educación en Enfermería, 2013)
<!-- [if gte mso 9]> <![endif]--> Objective. To describe and analyze the participation of students in the development of the pedagogical project (PP) in a Nursing program. Methodology. Exploratory-descriptive study with a qualitative approach, undertaken in the nursing program of a public higher education institution located in Piaui (Brazil). Interviews were carried out with twenty-two students from the 4th academic period onwards. Data collection took place in December 2009. The analysis of textual data was performed using the software Alceste 4.7, which was discussed based on the concepts of commitment, awareness, culture, dialogue and Paulo Freire’s problematization pedagogy. Results. The analysis revealed three classes: Students’ knowledge about the PP, collective participation in the development of the PP and progress of students’ participation in the development of the PP. Conclusion. The results show that students are participants in the development of the PP. <!-- [if gte mso 9]> Normal 0 21 false false false ES-CO X-NONE X-NONE <![endif]--><!-- [if gte mso 9]> <![endif]--><!-- [if gte mso 10]> <![endif]-->